If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 9 = -57 + -6x Reorder the terms: 9 + 5x = -57 + -6x Solving 9 + 5x = -57 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 9 + 5x + 6x = -57 + -6x + 6x Combine like terms: 5x + 6x = 11x 9 + 11x = -57 + -6x + 6x Combine like terms: -6x + 6x = 0 9 + 11x = -57 + 0 9 + 11x = -57 Add '-9' to each side of the equation. 9 + -9 + 11x = -57 + -9 Combine like terms: 9 + -9 = 0 0 + 11x = -57 + -9 11x = -57 + -9 Combine like terms: -57 + -9 = -66 11x = -66 Divide each side by '11'. x = -6 Simplifying x = -6
| 4(x-8)+6(5x+10)= | | 1xX^12=1.105 | | (x+5)(2x-1)(x-2)= | | sin(x)=5 | | sinx=5 | | (12x^3-7x^2+4x)-(5x^3-x^2-2)= | | 3m-n=7 | | s-10=20.01 | | 12c+8=20c-32 | | (x^2-8x+7)-(2x^2-5x-6)= | | 3x-5x=-5 | | (6x^3-x^2+11x)+(3x^3-9x+6)= | | -5v-7=10v+22 | | 15x=20-5x | | (4x^2+3x-5)+(2x+4)= | | 4/y+3=11 | | 10n+8=6n+20 | | 5x+5=5x-8 | | -5=2m+3 | | (x-1)(x+1)(x-6)= | | -16=-12 | | 9y+4=6y-4+3y | | -5=(2m+12b)3 | | 14m-93=49-57a | | 4y-2=y | | -5=(2m+12b) | | -5=2m | | -14+5x=3x-2 | | 12s+6-3s=6s+3s+6 | | =1E-05x^2+0.5798x+5415.1 | | (4x-1)(7x+2)= | | (7x+4)(2x-4)= |